Ext JS 4 Plugin and Extension Development. - Al Mohammad, Abdullah (Packt Publishing, 2013)
This is a step-by-step tutorial that practically teaches Ext JS plugin and extension development through sample examples that increase in complexity. Ext JS 4 Plugin and Extension Development is ideal for experienced ExtJS developers who want to expand their knowledge in developing plugins and extensions. This book is also for those developers who are new to ExtJS development, with at least some knowledge on ExtJS basics.